HISTOLOGICAL CONSEQUENCES OF CONSUMPTION OF ENERGY DRINK ON RENAL TUBULES - Ammara Rasheed (Army Medical College Rawalpindi, 2021)
Objective: To investigate the outcomes of energy drink on renal tubules of albino rats.